Implementing Task-Based Learning (TBL) to Develop Speaking Skill - Adzani , Feny Nur; Marhum, Mochtar; Dewi, Anjar Kusuma; Arid, Muhammad (Yayasan Kyadiren, 2024)
This study aims to determine whether the Task-based Learning (TBL) strategy can improve the speaking skills of 11th-grade students at MAN 2 Palu City. Using quantitative methods with a quasi-experimental design, the study involved 428 students as the population. The sample was selected purposively, with XI MIPA 1 serving as the experimental group and XI MIPA 3 as the control group. The research instrument consisted of pre-tests and post-tests. The results indicate a significant improvement in students' speaking skills after implementing TBL, as the t-value (4.092) exceeded the t-critical value (1.996) at a significance level of 0.05 with df=67. The hypothesis was accepted, confirming that TBL is effective in enhancing students' speaking abilities. Thus, this strategy can be applied as a teaching approach to foster speaking skill development.